O processo de internacionalização do ensino superior: um estudo de caso na Universidade Federal do Ceará - Nunes, Francisca Waleska Bruno (2018)
The influence of globalization on the world economy has had effects in several spheres of society, including Higher Education Institutions (HEIs) that have been driven to begin the process of internationalization in order to meet global demands. In this context, the Federal University of Ceará (UFC) walks in the feeling of being a reference in the challenges and solutions of the economic, market, educational, cultural, social and environmental areas. This study aims to analyze the process of internationalization of higher education in the UFC, throught the internationalization model of Knight (1994). It characterizes the nature of the research as applied, and as far as its objective is descriptive. In terms of obtaining information, it can be classified as bibliographical, documentary and field. The research strategy adopted was the case study, in which the university itself was the unit of analysis. Data collection was secondary by means of bibliographical and documentary research; and the primary through a single semistructured interview script that was based on the scripts of Miura (2006) and Batista (2009), which in turn had a theoretical basis in Knight (1994). The interview script was applied to the following research subjects: rector, vice-chancellor, pro-rectors (from the postgraduate, postgraduate and international relations) and directors of centers between August and November 2017. The study was organized in three parts: part one - context, awareness and commitment; part two - planning, operationalization and implementation; and, part three - revision, reinforcement, integration effect. Regarding the first part of the research, the external context of the pressures of globalization, the World Bank (WB), the World Trade Organization (WTO) and the United Nations (UN) urged internationalize. Regarding the internal context, the UFC institutionalized internationalization with the creation of the International Relations Office (PROINTER), the Internationalization Plan (NIP) and the Internationalization Committee (COMINTER) in 2017. Regarding the dimensions of awareness and compromise, both are fragile and require formalization of stimulus and engagement policies among administrative and academic units, as well as of all that compose the university community. Concerning the second part of this study, it was found that the UFC PIN contributed to the planning dimension, from the establishment of objectives and strategies. With regard to the operational and implementation dimensions, the UFC has encountered limitations on the bureaucracy of administrative and academic processes, on the promotion, empowerment and learning of other languages. About the third part, the analysis showed that, as far as the review dimension is concerned, the university does not have an evaluation system with its own methodology and indicators. As for the reinforcement and integration dimensions, the UFC needs both concrete and symbolic reinforcement policies and strategic actions to integrate the different units. More broadly, it has been observed that the university goes through a transitional period of the "ad hoc" national approach; to the "strategic"; and from the institutional "activity" approach to "procedural".